ANALISA PATAHAN PLANETARY PINION GEAR TRANSMISI DI UNIT EXCAVATOR PC 300 LC-7 KOMATSU - Saharil Saharil; Achmad Kusairi Samlawi (Universitas Lambung Mangkurat, 2019)
Gears are one of the engine components in the transmission system which functions to forward power from the drive shaft to the shaft to be moved. The speed ratio of the driving gear with the gear that is driven depends on the number of gears of each gear. Fault (Fracture) is the separation of a component or material into two or more parts, Ductile and brittle are the relative terms of certain faults, one type or another depending on the situation, the ductile fracture surface has its own characteristic in the macroscopic. The ductile fracture in the specimen leads to a point. The brittle fracture does not have plastic deformation. Decohesive rupture is a fault that occurs due to environmental reactions Autodesk Inventor is software development from its predecessor software in the CAD field, such as AutoCad and Mechanical Desktop. This software is made with various advantages with its predecessor software. The fracture on the planetary pinion gear Transmission in the pc300lc-7 excavator unit occurs because of the severe load that occurs at the operation, based on von misses analysis can be known (15,57 Mpa), principal stress (9,046 Mpa), and von misses stress with moment twisting (3,088 Mpa) is much smaller than the material elasticity limit of 689 MPa so that there is no stress concentration. The mechanism of failure occurs starting from the shock load in the material without any elastic deformation.